The Influence of Gadget Use on Early Childhood: Impacts and Strategies for Balanced Development - Azzah Shafa; Hafidz; Aulia Desti; Kharisma Dikta; Zahra Dian; Aisyah Azzahra; Nabila Sagita; Kania Rahma (Bulletin of Islamic Research, 2025)
This study explores the influence of gadget use on early childhood development, emphasizing both its positive and negative impacts. With the rapid advancement of technology, gadgets have become integral to modern life, providing educational resources, communication tools, and entertainment. However, excessive and unsupervised gadget use among children poses significant risks, including social detachment, delayed cognitive and emotional development, and reduced physical activity. Using descriptive and quantitative methods combined with a literature study, this research aims to analyze the effects of gadget use on children's social, emotional, and cognitive growth. The study also examines parental roles in managing gadget exposure and offers strategies to mitigate its adverse effects. Findings reveal that while gadgets offer educational benefits and enhance access to information, overuse can lead to dependency and hinder the social development of children. Parental guidance, such as setting screen-time limits, encouraging interactive play, and fostering balanced gadget use, is critical to ensuring a positive developmental trajectory. This research underscores the importance of responsible technology integration to promote holistic growth in early childhood.